Sins of the flesh : a history of ethical vegetarian thought - Preece, Rod, 1939- (UBC Press, 2008)
From the Publisher: Unlike previous books on the history of vegetarianism, Sins of the Flesh examines the history of vegetarianism in its ethical dimensions, from the origins of humanity through to the present. Full ethical consideration for animals resulting in the eschewing of flesh arose after the Aristotelian period in Greece and recurred in Ancient Rome, but then mostly disappeared for centuries. Despite the occasional presence of ascetic and cultural vegetarianism, it was not until the turn of the nineteenth century that vegetarian thought was revived and enjoyed some success; it subsequently went into another period of decline that lasted through much of the twentieth century. The authority-questioning cultural revolution of the 1960s brought a fresh resurgence of vegetarian ethics that continues to the present day.